MICROZONATION MAPS FOR KUALA LUMPUR AND PUTRAJAYA (Malaysian Journal of Civil Engineering, 2018)
Geotechnical factors often exert a major influence on damage patterns and loss of life in earthquake events. Even within an area of a city, building response and damage are varied significantly due to variation of soil profiles in that particular city. The existing codes or provisions, which were applied in a certain region, may not be necessarily employed directly in other region since individual region has its own characteristics. Therefore, it would be necessary to perform seismic hazard analysis for each region and to develop seismic design code that is suitable with the characteristics of that particular region rather than adopting the existing code. This paper presents the results of microzonation study for Kuala Lumpur city center and Putrajaya in Peninsular Malaysia. The microzonation study consists of two stages: (1) determination of the local geological and local geotechnical site conditions; and (2) computation of the ground response through soil deposit from base rock motions. Ground response analyses were performed using one dimensional shear wave propagation method. The analyses were conducted using nonlinear approach in order to consider the actual nonlinear response of a soil deposit. The results show that the accelerations at the surface of Kuala Lumpur city center are in the range of 90 to 190 gals and 180 to 340 gals for 500 and 2,500 years return periods, respectively. The accelerations at the surface of Putrajaya are in the range of 130 to 190 gals and 220 to 340 gals for 500 and 2,500 years return periods, respectively. Generally, the amplification factors on each city for those two hazard levels, ranges between 1.2 and 2.6. As a conclusion for this study, eight microzonation maps have been produced for each city that could be used as input for seismic design, land use management, and estimation of potential liquefaction and landslides.